2022
DOI: 10.1111/ijn.13101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the instrumental reminiscence therapy based on Roy's adaptation model on adaptation, life satisfaction and happiness in older people: A randomized controlled trial

Abstract: Aim This trial aimed to evaluate the effects of instrumental reminiscence therapy based on Roy's adaptation model on adaptation, life satisfaction and happiness in older people. Background Reminiscence therapy is one of the nursing interventions that facilitates the adaptation of older people to the process of ageing. Design The study utilized a pretest–posttest randomized controlled trial design. Methods This study was conducted at two nursing homes in Northern Cyprus between April and June 2021. The trial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This suggests that the RAM framework effectively addresses the psychological distress associated with surgical procedures [ 18 ]. Similarly, studies in patients undergoing bariatric surgery and instrumental reminiscence therapy based on RAM have demonstrated positive effects on physical activity, energy, adaptation, life satisfaction, and happiness [ 19 , 20 ]. Consistent with these findings, our study showed a significant decrease in anxiety and depression levels among elderly patients with BPH who received the RAM intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the RAM framework effectively addresses the psychological distress associated with surgical procedures [ 18 ]. Similarly, studies in patients undergoing bariatric surgery and instrumental reminiscence therapy based on RAM have demonstrated positive effects on physical activity, energy, adaptation, life satisfaction, and happiness [ 19 , 20 ]. Consistent with these findings, our study showed a significant decrease in anxiety and depression levels among elderly patients with BPH who received the RAM intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The Life Satisfaction Index-A (LSIA) was used to measure perceived life satisfaction. The total score of LSIA ranges from 0 to 20, and higher score indicates better life satisfaction (Aydogdu, 2023(Aydogdu, #1753.…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%
“…Twenty-two RCTs, involving 1098 participants, examined the effects of life review and reminiscence therapy on life satisfaction using the Life Satisfaction Index-A (LSI-A) [21,22,24,[29][30][31][33][34][35]41,43,48,49,51], the Satisfaction With Life Scale (SWLS) [20,40], the Life Satisfaction in the Elderly Scale (LSES) [28], and the Revised Philadelphia Geriatric Center Morale Scale (RPGCMS) [26]. The results showed that significant standardized mean differences existed in life review and reminiscence therapy compared with controls for life satisfaction (SMD 1.12; 95% CI 0.63 to 1.60; I 2 = 91.90%; p < 0.001) (Figure 4).…”
Section: Life Satisfactionmentioning
confidence: 99%
“…Meta-regression and subgroup analysis were then conducted respectively for continuous variables and categorical variables to investigate the potential drivers of heterogeneity. [20][21][22]24,26,[28][29][30][31][33][34][35]40,41,43,48,49,51].…”
Section: Meta-regression and Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation